(untitled) (Razi Medical Journal, 2025)
We conducted a prospective cohort study in 2024 at Al-Rasheed and Al-Mosarah Clinics. A total of 50 patients undergoing unilateral primary TKR were divided into two equal groups. One group received IV TXA (1g pre-op and 1g intra-op), while the other group received 1g IV TXA pre-op and 2g IA TXA intra-op. We measured Hb before surgery, and again on postoperative day 1 and day 2. The Hb drop was compared using SPSS software. The IA group had a lower average Hb drop on both days. On day 1, the mean drop was 1.55 g/dL in the IA group versus 1.82 g/dL in the IV group (p = 0.159). On day 2, the IA group had a mean drop of 2.09 g/dL versus 2.51 g/dL in the IV group (p = 0.056). Although day 1 results were not statistically significant, the day 2 results came close to statistical significance, favoring the IA group. Intra-Articular TXA may offer better control of blood loss after TKR, especially noticeable by day 2. The difference was not statistically significant, but the trend suggests IA TXA could be more effective over time. Larger studies are needed to confirm these findings.